Strategi Dakwah Islam dalam Pengembangan Seni dan Peradaban - Yahya, Wildan (FIkom Unisba, 2007)
As a distinctive feature of Islamic civilization, art become a way for communicating Islamic principles. The real essence of art is al-Tauhid which comes up from light chemical reactions. Al Tauhid has two aspects: the methodology and conceptual. The art of Islam itself has functions like these: reminder of tauhid, material transfiguration, structure transfiguration, and beauty.